STRATEGI PENCAPAIAN TARGET PELATIHAN PENYULUH KEAMANAN PANGAN DAN DISTRIC FOOD INSPECTOR TAHUN 2024 DENGAN PEMODELAN SISTEM DINAMIS - Perdhana Ari Sudewo (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2021)
Food and drug control, which is currently dominated by the supervision of processed food products in Indonesia, is still not optimal, so it is necessary to strengthen various aspects of implementation. In the 2020-2024 mid-term development plan, certification of Human Resources of food and drug control is set as a national priority program in strengthening food and drug control with a target of 4,400 certified by 2024, divided into 2,160 Pharma and Food Supervisors (PFM) and 2,240 Food Safety Extension Officers (PKP) and District Food Inspectors (DFI). In 2020, only 123 alumni of PKP and DFI training achieved than 320 people that targeted. This study aims to analyze the strategy for achieving PKP and DFI training targets in 2024 with a dynamic system modeling approach by evaluating the relationship between variables that influence the training system through behavioral analysis generated from the model building. From the four simulations carried out, it was found that all simulations did not impact training achievement but had an impact on the needs of the training facilitators. The simulation by increasing the facilitator's capacity so that one class is enough to be taught by four people from previously taught by eight people shows no impact on the need for additional facilitators at the Indonesian FDA. Furthermore, the simulation by changing the number of participants per class from 20 to 30 people shows the need for additional facilitators compared to the other simulations, namely four additional facilitators until 2024. The results from the system dynamics modeling of training are expected to be input for determining the PKP and DFI training system to achieve the target by the end of 2024.